Genetic polymorphisms offer insight into the causal role of microRNA in coronary artery disease. (February 2018) - Borghini, Andrea; Andreassi, Maria Grazia
Abstract: There is growing interest in the potential of circulating microRNAs (miRNAs), a class of small and noncoding RNA molecules, as diagnostic and/or prognostic biomarkers in coronary artery disease (CAD). Despite this promising role, there are still widespread inconsistencies among studies, and important obstacles must be overcome before miRNAs can enter clinical practice. The study of single nucleotide polymorphisms (SNPs) in the miRNA regulatory network could help shed light on the causality of associations as well as validate the value of cardiovascular miRNAs. SNPs in miRNA biogenesis or miRNA targetome genes may affect miRNA expression and circulating levels or the fidelity of the miRNA-mRNA interaction, influencing susceptibility to atherosclerotic vascular disease. This review aims to provide a general overview of the available studies that have investigated the association of miRNA gene polymorphisms with the susceptibility to CAD development and progression, and to highlight potential future research perspectives. Highlights: It is crucial to identify new markers for diagnosis, treatment and prognosis of CAD. Several obstacles must be overcome before miRNAs can enter clinical practice. The study of genetic variants in miRNA regulatory networks is a viable alternative. The review provides insight into the impact of SNPs in miRNA pathways on CAD.